ANALISIS PERSEPSI PENGGEMAR SEPAKBOLA TERHADAP TEKNOLOGI VAR DALAM PENGAMBILAN KEPUTUSAN YANG TEPAT - Sitanggang, Andris Sahata; Rizaldy, Andhika Rizqi; Dzikri, David Rizal; Abdurasyar, Rayhan; Bryan, Joe (Jurnal Ilmiah Sistem Informasi, 2024)
VAR (Video Assistant Referee) technology is a system implemented in football to assist referees in making important decisions during matches. This includes situations such as disallowed goals, penalties, red cards, and other important incidents. VAR technology utilizes video cameras and direct communication between the referee on the pitch and the VAR team off the pitch to provide an additional perspective on the situation. The goal of VAR technology research is to continuously improve the quality, efficiency, and acceptance of the technology in the world of football, with the ultimate goal of improving the fairness and integrity of the game. The research methods that researchers use are literature and descriptive methods